Optimization and determination of Tartrazine by Green Tween-20 cloud point extraction for food samples / Nurulhazirah Mohd Nasir... [et al.] - Mohd Nasir, Nurulhazirah; Asman, Saliza; Md Saleh, Noorashikin; Mohamad Zain, Nur Nadhirah (Universiti Teknologi MARA, Negeri Sembilan, 2019)
A simple and low-cost cloud point extraction (CPE) method was developed for the determination of tartrazine in food samples by spectrophotometry detection at a wavelength 427.5 nm. The CPE was performed by utilizing Tween-20 and sodium carbonate (Na 2 CO 3 ) as extractant and separation accelerator, respectively. Factors that influenced CPE such as surfactant and salt concentrations, pH and temperature were optimized in the context of extracting tartrazine from aqueous media. Under an optimal condition, the proposed CPE was applied for the determination of tartrazine in sweets and concentrated syrup juice, which represented food samples. A CPE-UV-Vis method showed linear calibration within the range of 1-12 mg L -1 of tartrazine with a regression coefficient was 0.9957. The limit of detection (LOD) and limit of quantification (LOQ) of the method were 0.88 mg L -1 and 2.96 mg L -1 , respectively. The relative standard deviation (RSD) was found to be < 3.00 %. The amount of tartrazine found in food samples was 1.22-6.12 mg L -1 . The results showed that the proposed CPE method was applicable for the determination of tartrazine in food samples and the tartrazine content in the food samples was permitted according to the guidelines from the European Food Safety Authority (EFSA).